2017
DOI: 10.1111/jpm.12382
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of training nurses in motivational interviewing to improve patient experience in mental health inpatient rehabilitation: a pilot study

Abstract: Introduction There is limited research addressing the experiences of patients in inpatient rehabilitation (rehabilitation), who often spend long periods in hospital, and the nursing approaches utilized. Aim Based on evidence that motivational interviewing (MI) may improve nursing practice, this was a pilot study evaluating the feasibility of training rehabilitation nurses in MI and measuring patient experience. Method Nurses underwent training and supervision focusing on MI spirit. Quantitative and qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…Practitioners were reasonably confident with the use of motivational interviewing techniques. As observed in previous studies [14, 29] some described difficulty with altering their established consultation style. Learning to pace was the most commonly reported self-management technique which patients and practitioners worked on together, followed by gaining control over pain and fatigue.…”
Section: Discussionsupporting
confidence: 58%
“…Practitioners were reasonably confident with the use of motivational interviewing techniques. As observed in previous studies [14, 29] some described difficulty with altering their established consultation style. Learning to pace was the most commonly reported self-management technique which patients and practitioners worked on together, followed by gaining control over pain and fatigue.…”
Section: Discussionsupporting
confidence: 58%
“…One program identified as a compassion education intervention in our literature searches mapped to the seeking to understand and relational communication domains as well as the virtuous response domain 148 of the Patient Compassion Model. 32 This program applied motivational interviewing techniques to promote person-centered care through active listening, validating patients’ views, and motivating patients to act as agents of change as opposed to providing advice to or persuading patients.…”
Section: Resultsmentioning
confidence: 99%
“…Patients reported that motivational interviewing techniques helped them feel more accepted by and to develop partnerships with their nurses. 148 …”
Section: Resultsmentioning
confidence: 99%
“…At the healthcare system level, compassion training was predominantly triggered by system-related failures characterized by: poor leadership and team practices [ 18 , 83 87 ]; a culture that favored high patient throughput over the relational aspects of care [ 88 , 89 ]; and patient complaints about gaps in the provision of compassionate care [ 90 , 91 ]. At the individual healthcare provider level, compassion training addressed the need to: nurture innate compassion; reduce learner stress; and improve learner clinical competence.…”
Section: Resultsmentioning
confidence: 99%